ANALISIS PENGARUH LIKUIDITAS, STRUKTUR MODAL DAN SKALA PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD AND BEVERAGES DI BEI PERIODE 2009-2012 - Ika Jaya Mulya Desfrains, 10.05.51.0007 (Students Journal of Economic and Management, 2014)
This study is a study that examines the effect of liquidity, capital structure and scale the company to profitability in Food and Beverages company in BEI 2009-2012.The results of the first study showed that the positive and significant effect of liquidity, the higher the liquidity will increase the profitability of the company. The results of both studies showed that the capital structure and significant positive effect on profitability so that loans obtained from third parties can be used optimally in improving the profitability of the company. While the results of the three studies showed that the scale of the company and no significant negative effect on profitability, the more extensive the company is not going to determine the high profitability of the acquisition on the company, but may be determined by other factors. Keywords : Liquidity, Capital Structure, Corporate Scale, Profitability